Comparison of physicochemical properties of date seed from solvent extraction and supercritical fluid extraction - Mohd Jaih, Abdul Afiq (2014)
Date seed is a by-product of date fruit industry, which is normally being discarded, or traditionally used as animal feed ingredient or turned into noncaffeinated coffee by the Arabs. In this study, oil samples were extracted from the seed of five varieties of mature date fruit namely Mabroum, Rotab, Mariami, Safawi and Sufri through Soxhlet extraction method. The extracted oil were analysed on its Iodine value (IV), fatty acid content (FAC), triacylglycerol (TAG) composition, as well as its thermal properties. The antioxidant properties in date seed oils (DSOs) were determined through total phenolic content (TPC) analysis, radical scavenging activity analysis and reducing power assay. Other than that, the DSO also was extracted through supercritical fluid extraction (SFE) technique. From the findings, it was found that Rotab seed has the highest oil content (9.75 ± 0.04 % of the date seed), while Mariami seed has the lowest oil content (8.04 ± 0.01 % of the date seed). The IVs of the five DSOs were ranged from 48.7 to 55.5 g I2/100g. The major fatty acids that were found in Mariami, Safawi, Rotab and Sufri seed oils were oleic acid, followed by lauric acid, while opposite major fatty acid content was found in Mabroum seed oil. The major TAG found in those five DSOs were LaOO (La: lauric acid; O: oleic acid). The differences in FAC, TAG and IV between the five varieties of DSO lead to variation in melting and solidification properties of the oils. Analysis of antioxidant content showed that the total phenolic contents in the five DSOs were in the range of 7.962 to 17.724 mg GAE/g oil. The analysis on antioxidant activity found that its capability to terminate the radical activity of DPPH that were expressed as 50 % effective concentration (EC50) ranged from 5.170 to 17.175 mg/ml. Moreover, the reducing power analysis found that the highest reducing activity was obtained at concentration 4 mg/ml. In SFE technique, the combination of 40 oC and 20 MPa of the extraction parameters resulted in the highest oil yield. The oil yield obtained through this technique ranged from 4.28 to 8.10 %. Oleic acid was found as the only major fatty acid present in the DSO extracted through SFE technique. Overall, the findings of the present study suggest that the DSOs are potentially to be developed as a new functional oil product due to its properties and SFE can be a technique in producing halalan thoyyiban oil product.